Effects of tomato leaves allelochemicals on tomato borer (Tuta absoluta Meyrick) in Tlemcen region, Algeria - Bouklikha, A. (2018)
We investigated the qualitative and quantitative composition of phenolic compounds in tomato (Lycopersicon esculentum Mill L.) leaves with and without infestation of tomato borer (Tuta absoluta Meyrick). Infested and healthy leaves of tomato were extracted with aqueous methanol, which was partitioned with ethyl acetate and n-butanol. Infested leaves contained higher levels of total phenolics, flavonoids, flavonols and tannins. The HPLC analysis of the nbutanol fraction indicated that the leaves contained the catechin and two unknown compounds, which are likely to be phytoalexins. The protective role of these molecules need to be investigated, to incorporate this finding in the tomato breeding programmes against the tomato borer.